What Are the Risks of Contracting Diseases Associated with Chickens? - C. Roxanne Rutledge-Connelly; Christopher Mores; Amy H. Simonne (EDIS)
Some diseases of animals are communicable to humans. The microorganisms that cause disease can be protozoal, fungal, bacterial, chlamydial or viral (Jacob et al. 2003). Some examples of avian diseases transmissible to humans include Chlamydiosis from parakeets, pigeons, and parrots and Cryptococcosis from pigeons. Salmonella, E. coli, the viruses that cause Avian Influenza, and some encephalitis viruses are associated with chickens. This document is ENY-724, one of a series of the Department of Entomology and Nematology, UF/IFAS Extension. Original publication date September 2005.